Does the Development of Renewable Energy and Smart Grids Pose Risks for Russian Gas Projects? Scenario Forecast for Partner Countries - Ratner, Svetlana V.; Khrustalev, Evgenii Yu.; Larin, Sergey N.; Khrustalev, Oleg E. (International Journal of Energy Economics and Policy, 2019)
In this article we examine the risks of reducing the consumption of natural gas in the countries that are the largest exporters of Russian natural gas (Germany, Italy, Turkey, China) caused by the development of renewable energy. The forecast of natural gas consumption is built up to 2030 by extrapolating the trend of time series, while selecting the type of trend takes into account the S-shaped development of new energy technologies. Two scenarios are considered: the first involves the development of the electric power industry in the way of “business as usual”, while the second takes into account the development of intelligent grids and the Internet of energy (IoE). The results show that the intensive development of renewable energy in combination with the digitalization of electric grids can create the most significant risks for the development of gas energy in Germany and Turkey. In Germany, these risks are determined to a greater extent by the desire of the authorities to maintain the achieved level of energy security, which will inevitably fall with a decrease in coal generation and an increase in the share of gas. In Turkey, these risks are determined by the purely technical and technological development of the country, its dynamics and nature. Keywords: renewable energy, natural gas exports, risk analysis, forecast JEL Classifications: O33, Q42, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.8627